Amyotrophic lateral sclerosis-immunoglobulins selectively interact with neuromuscular junctions expressing P/Q-type calcium channels - Gonzalez, Laura Elisabeth (2011)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by a gradual loss of motoneurons. The majority of ALS cases are associated with a sporadic form whose etiology is unknown. Several pieces of evidence favor autoimmunity as a potential contributor to sporadic ALS pathology. To gain understanding concerning possible antigens interacting with IgGs from sporadic ALS patients (ALS-IgGs), we studied immunoreactivity against neuromuscular junction (NMJ), spinal cord and cerebellum of mice with and without the Ca V2.1 pore-forming subunit of the P/Q-type voltage-gated calcium (Ca 2+) channel. ALS-IgGs showed a strong reactivity against NMJs of wild-type diaphragms. ALS-IgGs also increased muscle miniature end-plate potential frequency, suggesting a functional role for ALS-IgGs on synaptic signaling. In support, in mice lacking the Ca V2.1 subunit ALS-IgGs showed significantly reduced NMJ immunoreactivity and did not alter spontaneous acetylcholine release. This difference in reactivity was absent when comparing N-type Ca 2+ channel wild-type or null mice. These results are particularly relevant because motoneurons are known to be early pathogenic targets in ALS. Our findings add further evidence supporting autoimmunity as one of the possible mechanisms contributing to ALS pathology. They also suggest that serum autoantibodies in a subset of ALS patients would interact with NMJ proteins down-regulated when P/Q-type channels are absent. © 2011 International Society for Neurochemistry.